2021
DOI: 10.1155/2021/4188178
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Chest CT Scan as a Screening and Diagnostic Tool in Trauma Patients with Coronavirus Disease 2019 (COVID-19): A Cross-Sectional Study

Abstract: Background. The lack of enough medical evidence about COVID-19 regarding optimal prevention, diagnosis, and treatment contributes negatively to the rapid increase in the number of cases globally. A chest computerized tomography (CT) scan has been introduced as the most sensitive diagnostic method. Therefore, this research aimed to examine and evaluate the chest CT  scan as a screening measure of COVID-19 in trauma patients. Methods. This cross-sectional study was conducted in Rajaee Hospital in Shiraz from Feb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
(23 reference statements)
0
9
0
Order By: Relevance
“…Health systems have undergone many changes with the global onset of the COVID-19 epidemic [ [19] , [20] , [21] , [22] ]. Hospitals postponed non-urgent surgeries, including arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…Health systems have undergone many changes with the global onset of the COVID-19 epidemic [ [19] , [20] , [21] , [22] ]. Hospitals postponed non-urgent surgeries, including arthroplasty.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation for the high false-positive rate of chest CT in asymptomatic patients is that many diseases can radiologically mimic COVID-19 pneumonia, including other forms of viral pneumonia [ 22 , 23 ], atypical pneumonia [ 24 ], interstitial pneumonia [ 3 , 8 , 12 , 21 , 22 ], drug-induced pneumonia [ 21 , 25 , 26 ], and traumatic changes such as rib fractures [ 27 ]. Our results suggested that unknown early or mild interstitial pneumonia and bilateral lower lobe dorsal lung collapse due to poor inspiration were difficult to differentiate from mild COVID-19 pneumonia, which supports the findings of previous reports [ 3 , 8 , 12 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are several COVID-19 vaccines available worldwide that have demonstrated high effectiveness in preventing the infection and lowering COVID-19-related deaths ( 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ). The preoperative vaccination could significantly reduce the risk of COVID-19 complications, thus enabling elective surgery to be performed safely ( 17 , 28 , 29 , 30 ). In order to perform a safe surgical procedure, there must be a minimum amount of nosocomial transmission.…”
Section: Introductionmentioning
confidence: 99%